THERMODYNAMICS ANALYSES ON REGENERATIVE STEAM CYCLE WITH TWO TANKS FOR HTGR-10 CONCEPT - Sri Sudadiyo; Geni Rina Sunaryo (Website, 2017)
In this work, steam cycle from a nuclear power plant is explored in order to increase efficiency and electric power output. A thermal source in the form of a HTGR-10 concept is considered. The power conversion unit of HTGR-10 consists of steam generator, turbine, condenser, pump, and connecting pipes. Helium is used as the core coolant and the working fluid for power conversion unit is water/steam. The proposed thermodynamic process modification has been evaluated for regenerative steam power cycle of this reactor. The scope of study covered regenerative steam cycle with two tanks including feed water tank and intermediate feed water tank. The evaluation analyzes the effect of pressure, efficiencies of turbine and pumps, and tanks against thermal efficiency. The Cycle-Tempo software is used to simulate and optimized this effect on steam cycle based on HTGR-10. The results indicate improvements of as much as 2.65 % in thermal efficiency and 0.271 MWe in electric power.